2000
DOI: 10.1089/089771500415391
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Damage: Serum S-100 Protein Measurements Related to Neuroradiological Findings

Abstract: This study was designed to investigate the correlation between S-100 protein serum measurements and neuroradiological findings in patients with head injury. We studied 278 patients with minor, moderate, and severe head injuries and 110 controls with no history of neurological disease. The study recruited patients from three Scandinavian neurotrauma centers. Serum levels of S-100 protein were measured at admittance, and computed tomographic scans of the brain were obtained within 24 h postinjury in all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
105
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(115 citation statements)
references
References 25 publications
6
105
1
3
Order By: Relevance
“…Numerous reports in the literature document the usefulness of measuring glial fibrillary acidic protein in CSF as a specific indicator of CNS pathological abnormalities (Eng et al, 1971;Eng 1980;Aurell et al, 1991;Blennow et al, 1996). S-100b, the principal low-affinity calcium-binding protein in astrocytes (Xiong et al, 2000), was reported to consistently correlate with both GCS score and neuroradiological findings at admission (Raabe et al, 1999b(Raabe et al, , 1998Romner et al, 2000;Woertgen et al, 1999). Nevertheless S100b, initially considered unique to the nervous system, is present in other tissues including adipocytes and chondrocytes.…”
mentioning
confidence: 99%
“…Numerous reports in the literature document the usefulness of measuring glial fibrillary acidic protein in CSF as a specific indicator of CNS pathological abnormalities (Eng et al, 1971;Eng 1980;Aurell et al, 1991;Blennow et al, 1996). S-100b, the principal low-affinity calcium-binding protein in astrocytes (Xiong et al, 2000), was reported to consistently correlate with both GCS score and neuroradiological findings at admission (Raabe et al, 1999b(Raabe et al, , 1998Romner et al, 2000;Woertgen et al, 1999). Nevertheless S100b, initially considered unique to the nervous system, is present in other tissues including adipocytes and chondrocytes.…”
mentioning
confidence: 99%
“…Most of these studies have been conducted in adult and paediatric patients who had suffered head trauma of varying degrees. [4][5][6][7][8][9] Other studies ABSTRACT: Background: It has been shown previously that S-100β levels in serum correspond with the severity of central nervous system (CNS) trauma. It also has been suggested that S-100β in CNS tissue is involved in neuroprotection and neuroregeneration.…”
mentioning
confidence: 99%
“…16,17 Both the time course and the degree of elevation were associated strongly with neuropsychological outcome after cardiac surgery and head trauma. 9,10,12 Serum S100␤ levels also have been correlated with the volume of infracted brain in patients with stroke. 18,19 Although it is recognized that S100␤ originates from the central nervous system (CNS) and increases in cerebrospinal fluid (CSF) after injury, it remains unclear whether elevation of serum levels of S100␤ is a sign of bloodbrain barrier (BBB) dysfunction or neuronal/parenchymal damage.…”
mentioning
confidence: 99%